Endoscopic resection of a giant symptomatic Brunner’s gland hamartoma of duodenal bulb - Shrestha, Umid Kumar; Aryal, Gopi (Journal of Advances in Internal Medicine, 2019)
Brunner's gland hamartoma is a very rare benign tumor arising from the Brunner’s gland of duodenum and is usually asymptomatic, but may present with the symptom of duodenal obstruction or upper gastrointestinal bleeding due to ulceration from the tumor, requiring endoscopic or surgical resection. In our study, we report the case of a 57 year-old male who presented with pain over epigastrium, recurrent vomiting, black stool and dizziness with a lowering of hemoglobin up to 7.5 gm/dl. The blood transfusion was done to raise the hemoglobin. The upper gastrointestinal endoscopy revealed a giant submucosal polypoidal mass with a thick short stalk in duodenal bulb causing almost complete obstruction of the lumen of duodenum and there was a superficial ulceration on the under-surface of the mass. The endoscopic ultrasound revealed a submucosal lesion arising from the echo layer three. The computed tomography of abdomen showed that the polypoidal mass was confined to the duodenal lumen with no significant lumphadenopathy and normal biliary and pancreas. The endoscopic polypectomy was attempted, but the lesion was too large to grab the polyp as a whole with the conventional snare. Hence, the repeated partial snare polypectomies were done, followed by submucosal dissection to ensure the complete removal of the mass. There were no complications after the procedure. The histopathology examination of the duodenal mass confirmed the diagnosis of Brunner’s gland hamartoma and showed the presence of Helicobacter pylori as well. The endoscopic treatment of giant Brunner’s gland hamartoma avoided the need of unnecessary more invasive surgical procedure.